The Effect of Type of Birth, Sex and Castration on Body Weight and Body Linear Measurements in Pre-Weaning Kids - Tsado, D.N.; Adama, T.Z. (Pakistan Journal of Nutrition, 2012)
This study was conducted to determine the effect of castration, sex and type of birth on the rate of body weight gain and linear measurements non castrates, castrates and female Savanna Brown kids. The mean values of the body weight, body length and chest girth of single non-castrates (5.75kg, 53.37 cm and 42.50cm) were higher but not significantly different (p > 0.05) from other groups. Single castrates and twin castrates in height at withers (38.86cm and 38.47cm), significantly (p < 0.05) differed from that of the females (36.09cm). Singles (non castrates and castrates) shows a superior performance in body weight and body gain measurement, signifying the effect of type of birth. It was concluded that the influence of castration in this study did not appear significant, However, the sex influence appeared positive as males and castrates performed better in most parameters than females.